"Subclinical" pacemaker syndrome: a randomised study of symptom free patients with ventricular demand (VVI) pacemakers upgraded to dual chamber devices. Issue 1 (January 1992) - Sulke, N; Dritsas, A; Bostock, J; Wells, A; Morris, R; Sowton, E
Abstract : OBJECTIVE–To determine whether symptom free patients with single chamber pacemakers benefit from dual chamber pacing. DESIGN–A randomised double blind crossover comparison of ventricular demand (VVI), dual chamber demand (DDI), and dual chamber universal (DDD) modes after upgrading from a VVI device. SETTING–Cardiology outpatient department. PATIENTS–Sixteen patients aged 41-84 years who were symptom free during VVI mode pacing for three or more years. INTERVENTION–Pacemaker upgrade during routine generator change. MAIN OUTCOME MEASURES–Change in subjective (general health perception, symptoms) and objective (clinical assessment, treadmill exercise, and radiological and echocardiographic indices) results between pacing modes before and after upgrading. RESULTS–75% preferred DDD, 68% found VVI least acceptable with 12% expressing no preference. Perceived general well-being and exercise capacity (p less than 0.01) and treadmill times (p less than 0.05) were improved in DDD mode but VVI and DDI modes were similar. Clinical, echocardiographic, radiological, and electrophysiological indices confirmed the absence of overt pacemaker syndrome, although mitral and tricuspid regurgitation was greatest in VVI mode (p less than 0.01). CONCLUSIONS–Most patients who were satisfied with long term pacing in VVI mode benefited from upgrading to DDD mode pacing suggesting the existence of "subclinical" pacemaker syndrome in up to 75% of such patients. The DDI mode offered little subjective or objective benefit over VVI mode in this population and should be reserved for patients with paroxysmal atrial arrhythmias. VVI mode pacing should be used only for patients with very intermittent symptomatic bradycardia or atrial fibrillation with a good chronotropic response during exercise.